Prevalence and zoonotic potential of avian chlamydia in Croatia : Pojavnost i zoonotski potencijal klamidija ptica u Hrvatskoj - Horvatek Tomić, Danijela (Array, 2020)
Background: Zoonotic Chlamydia (C.) psittaci, can be found in different bird species, but also in other animals and humans. Recently, new species have been described, as C. gallinacea and C. avium, changing the perspective of a single causative agent of avian chlamydiosis. Genotypes of C. psittaci differ, according to their pathogenicity, and the ones isolated from parrots, turkeys and ducks are particularly pathogenic to bird breeders or owners, veterinarians, poultry farms and slaughterhouse workers. Infections in humans may pass unapparent or to the onset of systemic lung inflammation. Asymptomatic infection is most commonly found in birds, but acute systemic or chronic infections are also possible. Material and Methods: Presence of C. psittaci in birds in Croatia must be reported by law, and all registered flocks of pigeons, parrots and other birds must be examined once, and pet shops at least twice a year. In the period from 2008 to 2017, a total of 3283 avian samples were examined by real-time PCR and the presence of Chlamydiaceae, C. psittaci and C. gallinacea were detected in faecal samples or swabs. Results and Conclusions: In total, 12% of the samples were found positive for Chlamydiaceae. From the 2015, the presence of C. psittaci has also routinely been determined, whereas 34.01% positive avian samples proved to be C. psittaci. Findings of chlamydia in various avian species indicates the importance of proper implementation of the protective measures, by taking into account the zoonotic potential of chlamydia originating from birds and poultry.